Acute hepatitis in the scarlatina course. Case presentation - Ariel Uriarte Méndez; Andrés Prieto Apesteguía; Jesús Vila Díaz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
The case of a boy is presented with feverish square, associated to icterus and eruption micropapular generalized. The clinical and analytic valuation led to two very defined illnesses: scarlatina and acute hepatitis. The uncommon of the clinical square, led to revise the related medical literature and it was surprising the fact that this association had been found by several authors who outlined it as something uncommon, there were described a few cases in the world according to the medical reports, that constituted the motivation to give to know such discovery.